2014
DOI: 10.1002/2013gl059134
|View full text |Cite
|
Sign up to set email alerts
|

Low-water maps of the groundwater table in the central Amazon by satellite altimetry

Abstract: Groundwater plays a fundamental role in rainforest environments, as it is connected with rivers, lakes, and wetlands, and helps to support wildlife habitat during dry periods. Groundwater reservoirs are however excessively difficult to monitor, especially in large and remote areas. Using concepts from groundwater-surface water interactions and ENVISAT altimetry data, we evaluated the topography of the groundwater table during low-water periods in the alluvial plain of the central Amazon. The water levels are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…On the other hand, in order to avoid negative impacts of extreme events, it is also necessary to improve our understanding of hydrological physical processes and sensitivity to droughts and floods in the Amazon region, including in groundwater storage (e.g. Pfeffer et al, 2014), river/floodplain hydrodynamic and hydrology processes (e.g. Trigg et al, 2009;Rodriguez et al, 2010;Getirana et al, 2012;Guimberteau et al, 2012;Frappart et al, 2013;Tomasella et al, 2013;Rudorff et al, 2014a, 2014b, Paiva et al, 2013a.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in order to avoid negative impacts of extreme events, it is also necessary to improve our understanding of hydrological physical processes and sensitivity to droughts and floods in the Amazon region, including in groundwater storage (e.g. Pfeffer et al, 2014), river/floodplain hydrodynamic and hydrology processes (e.g. Trigg et al, 2009;Rodriguez et al, 2010;Getirana et al, 2012;Guimberteau et al, 2012;Frappart et al, 2013;Tomasella et al, 2013;Rudorff et al, 2014a, 2014b, Paiva et al, 2013a.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, altimetry data could be used to compute the interferometric bias with reasonable confidence if the study window is large enough to overlap a reasonable number of ICESat/GLAS points. Improvement of the flooding extent at the LW stage might also be induced, selecting the minimum values of altimetry data for the pixels overlapped by SWBD, following a similar method as proposed by Pfeffer et al [77].…”
Section: Usefulness Of Bathymetric Data In the Correction Processmentioning
confidence: 99%
“…This validation process was highly dependent on the length of the concomitant observations and on the distance to the closest gauge. Previous studies demonstrated the capability of radar altimetry to retrieve reliable water levels over water bodies larger than 200 or 300 m across [46,51,68,69], even over floodplains covered with vegetation [19,68,70]. At nadir incidence, the intensity of the returned power is weakly attenuated by the vegetation cover (at least for Leaf Area Index < 1.5; see [71]), even if the radar echo is impacted.…”
Section: Validation Of Altimetry-based Water Levelsmentioning
confidence: 99%